Studi Komparasi Pendidikan Gender di Pesantren (Studi Kasus Pondok Pesantren Salaf Baitul Atiq Karduluk dan Pondok Pesantren Modern Nurul Huda Pakandangan) - Jauharotul Makniyah; Laily Erliyanti (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2021)
This study aims to describe the forms of gender education in salaf and modern Islamic boarding schools, as well as the differences and similarities between the two. In this study, researchers used a qualitative approach with a multi-site case study type, namely the Salaf Islamic Boarding School (BaitulAtiq) and the Modern Islamic Boarding School (Nurulhuda).Sources of data from this study are two sources of data, namely primary / direct sources and secondary data sources / indirect sources. Data collection techniques through in-depth interviews, direct observation, and documentation. The validity test of the result data was done by using triangulation techniques.The gender education system at the Salaf Islamic Boarding School (BaitulAtiq) Karduluk is applied in several activities of Istighosahhirzih / morning study, chanting Al-quran, entering class, Diniyah / sifir school, yellow book study and night study. The gender education system at the Modern Islamic Boarding School (Nurulhuda) Pakandangan is implemented in the following activities: Tahajjud prayer, qira'atulqur'an, daily mufradhat, tandhifulbie'ah, going to class, muhadharah, and night study. The differences between gender education in the Salaf Islamic boarding school (BaitulAtiq) Karduluk with the modern Islamic boarding school (Nurulhuda) Pakandangan are: teaching materials system, boarding school educators / administrators and the education system. The similarity between gender education at the Salaf Islamic boarding school (BaitulAtiq) Karduluk and the Pakandangan modern Islamic boarding school (Nurulhuda) is only found in the rules of teaching teachers at formal schools. Penelitian ini bertujuan untuk mendeskripsikan bentuk pendidikan gender di Pesantren salaf dan modern, serta perbedaan dan persamaan antara keduanya. Dalam penelitian ini, peneliti menggunakan pendekatan kualitatif dengan jenis studi kasus multi situs yaitu pertama di Pondok Pesantren Salaf (Baitul Atiq) dan Pondok Pesantren Modern (Nurulhuda).Sumber data dari penelitian ini dengan dua sumber data, yaitu primer/sumber langsung dan sumber data sekunder/sumber tidak langsung.Teknik pengumpulan data melalui wawancara mendalam, observasi langsung, dan dokumentasi.Uji keabsahan data hasil dilakukan dengan triangulasi teknik. Sistem pendidikan gender di Pondok Pesantren Salaf (Baitul Atiq) Karduluk teraplikasi dalam beberapa kegiatan Istighosah hirzih/kajian pagi, Ngaji Al-qur’an, Masuk kelas, Sekolah Diniyah/sifir, kajian kitab kuning dan belajar malam. Sistem pendidikan gender di pondok Pesantren Pesantren Modern (Nurulhuda) Pakandangan adalah telaksana pada beberapa kegiatan berikut : Shalat tahajjud, qira’atul qur’an, mufradhat harian, tandhiful bie’ah, masuk kelas, muhadharah, dan belajar malam.Perbedaan antara pendidikan gender di pondok pesantren salaf (Baitul Atiq) Karduluk dengan pondok pesantren modern (Nurulhuda) Pakandangan adalah :sistem bahan ajar, tenaga pendidik/pengurus pondok dan sistem pendidikan. Persamaan antara pendidikan gender di pondok pesantren salaf (Baitul Atiq) Karduluk dengan pondok pesantren modern (Nurulhuda) Pakandangan hanya terdapat pada aturan guru pengajar pada sekolah formal.